1990
DOI: 10.1002/cyto.990110609
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of DNA content and keratins by using CK7, CK8, CK18, CK19, and KL1 monoclonal antibodies in benign and malignant human breast tumors

Abstract: We have used a double‐labelling flow cytometry analysis of keratin (CK) and DNA in breast cancer. Five monoclonal anti‐keratin antibodies were tested: KL1 recognizing Mr 55,000–57,000 keratins, and “anti‐glandular epithelia,” LE41, RGE‐53, and LP2K specific for CK n° 7, 8, 18, and 19 of Moll's classification, respectively. Flow cytometric (DNA‐CK) analysis was performed on 10 benign and 19 malignant human breast tumors. All the benign tumors were diploid and 63% of the malignant tumors were aneuploid. This tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Earlier reports from our group failed to demonstrate this relationship even in a univariate analysis (O'Reilly et al, 1990a-c), though all these studies had shown a trend for DNA aneuploidy to signify a poorer prognosis. Further, the results of the present study are in ine with the overview from the literature in that, while DNA ploidy is significntly ted to cinical outcome, the magnitude of the survival advantage of a DNA diploid tumour over an aneuploid one is small (Camplejohn and Macartney, 1992;Hedley et al, 1993 (Ferrero et al, 1990). Either method of removing normal cells from the analysis of SPF for DNA diploid tumours would be expected to improve further the prognostic power of this parameter.…”
supporting
confidence: 73%
“…Earlier reports from our group failed to demonstrate this relationship even in a univariate analysis (O'Reilly et al, 1990a-c), though all these studies had shown a trend for DNA aneuploidy to signify a poorer prognosis. Further, the results of the present study are in ine with the overview from the literature in that, while DNA ploidy is significntly ted to cinical outcome, the magnitude of the survival advantage of a DNA diploid tumour over an aneuploid one is small (Camplejohn and Macartney, 1992;Hedley et al, 1993 (Ferrero et al, 1990). Either method of removing normal cells from the analysis of SPF for DNA diploid tumours would be expected to improve further the prognostic power of this parameter.…”
supporting
confidence: 73%
“…Furthermore, some breast cancers may have diminished expression of keratins. However, the monoclonal antibody CAM 5.2 seems to be a useful tool for selecting tumour cells, since the majority of breast tumours express the simple epithelial keratins 8 and 18 (Nagle et al, 1986;Ferrero et al, 1990;Wetzels et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…The vast majority of normal and malignant mammary epithelial cells contain cytokeratins 7, 8, 18 and 19. The characteristics of cytokeratin in normal epithelia of the breast are mostly well preserved during malignant progression and, to some extent, even more pronounced in carcinomas (Osborn et al, 1983;Ferrero et al, 1990;Wetzels et al, 1991). A fluorescein isothiocyanate (FITC)-conjugated secondary antibody, together with a primary monoclonal antibody specific for cytokeratin, used with a suspension of cells with preserved antigenicity, allows flow cytometric sorting of the epithelial cell population (Zarbo et al, 1989;Visscher et al, 1990 1977 and 1990, were included in the study.…”
mentioning
confidence: 99%
“…One of the main features of transition from a normal to cancerous state has been reputed to be an alteration in the cytoskeletal structure (22), and the relative level of CK within a cell during this transition may be an important marker of disease. Using quantitative multiparametric flow cytometry the degree of CK staining may allow the detection of subtle changes in CK expression between normal and abnormal cells (15). Use of pan CK antibodies, which label more than one type of CK at a time, coupled with single-color immunohistochemical detection may not fully quantify the individual changes in each CK type that may occur during tumor development and progression.…”
mentioning
confidence: 99%